2022
DOI: 10.3389/fmicb.2022.982338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rumen bacterial communities between yaks (Bos grunniens) and Qaidam cattle (Bos taurus) fed a low protein diet with different energy levels

Abstract: The yak (Bos grunniens), an indigenous bovine on the Qinghai-Tibetan plateau (QTP), is reported to digest low quality forage to a greater extent and to require less protein and energy for maintenance than the introduced Qaidam cattle (Bos taurus). Ruminal bacteria play a major role in feed degradation, and therefore, we hypothesized that ruminal bacteria composition would differ between yaks and cattle, and confer an advantage to yaks for poor quality diets. To test our hypothesis, we determined the ruminal ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…This might be the reason for the greater acetic acid production in cows fed NCG. Moreover, greater milk fat contents were determined in Jersey cows offered same dose of NCG like the current study ( Liu H. et al, 2022 ; Liu Z. et al, 2022 ), suggesting that enhanced acetic acid are beneficial for milk fat syntheses. Dietary supplementation of NCG did not affect the molar proportion of propionate acid, thus lead to greater acetate to propionate ratio.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…This might be the reason for the greater acetic acid production in cows fed NCG. Moreover, greater milk fat contents were determined in Jersey cows offered same dose of NCG like the current study ( Liu H. et al, 2022 ; Liu Z. et al, 2022 ), suggesting that enhanced acetic acid are beneficial for milk fat syntheses. Dietary supplementation of NCG did not affect the molar proportion of propionate acid, thus lead to greater acetate to propionate ratio.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, it is widely used as a viable and cost-effective alternative to Arg. Our parallel study indicated that dietary supplementation of NCG by 20 g/d/head prevented hypoxic stress and tended to improve milk quality of Jersey dairy cows in Tibet ( Liu H. et al, 2022 ; Liu Z. et al, 2022 ). This suggests that NCG also has beneficial effects on the physiological regulation of introduced animals at high altitude plateau.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…DNA was quantified using the Qubit dsDNA BR Assay kit (Invitrogen, USA) and quality was assessed by running an aliquot on a 1% agarose gel. To amplify variable regions V1-V9 of the bacterial 16S rRNA gene, degenerate PCR primers 27F (5′-AGRGTTYGATYMTGGCTCAG-3′) and 1492R (5′-RGYTACCTTGTTACGACTT-3′) were used ( 14 ). Additionally, degenerate PCR primers ITS3 (5′-GCATCGATGAAGAACGCAGC-3′) and ITS4 (5′-TCCTCCGCTTATTGATATGC-3′) were used to amplify the ITS2 of the internal transcribed spacer (ITS) region ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…As the diet of FMD changes from consuming milk to eating plants, the richness and diversity of intestinal microbiota of young FMD increased significantly ( Li et al, 2021 ). What’s more, previous found that dietary protein levels not only affect the growth performance of ruminants, but also play an important role in regulating the microbial structure of the digestive tract ( Liu et al, 2022 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%